Post-Crisis Bank Liquidity Risk Management Disclosure - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2010)
Purpose This work seeks to investigate post-crisis measures banks have adopted in a bid to manage liquidity risk. It is based on the fact that the financial liquidity market was greatly affected during the recent economic turmoil and financial meltdown. During the crisis, liquidity risk management disclosure was crucial for confidence building in market participants. Design/methodology/approach The study investigates if Basel II pillar 3 disclosures on liquidity risk management are applied by 20 of top 33 world banks. Bank selection is based on information availability, geographic balance and comprehensiveness of the language in which information is provided. This information is searched from the World Wide Web, with a minimum of one hour allocated to 'content search', and indefinite time for 'content analyses'. Such content scrutiny is guided by 16 disclosure principles classified in four main categories. Findings Only 25% of sampled banks provide publicly accessible liquidity risk management information; a clear indication that in the post-crisis era, many top ranking banks do not still take Basel disclosure norms seriously, especially the February 2008 pre-crisis warning by the Basel Committee on Banking Supervision. Implications/limitations Bank stakeholders should easily have access to information on liquidity risk management. Banks falling-short of making such information available might not inspire confidence in market participants in events of financial panic and turmoil. Like in the run-up to the previous financial crisis, if banks are not compelled to explicitly and expressly disclose what measures they adopt in a bid to guarantee stakeholder liquidity, the onset of any financial shake-up would only precipitate a meltdown. The main limitation of this study is the use of the World Wide Web as the only source of information available to bank stakeholders and/or market participants. Originality/value The contribution of this paper to literature can be viewed from the role it plays in investigating post-crisis measures banks have adopted in a bid to inform stakeholders on their management of liquidity risk.
Keywords: D80; E50; G00; G18; 330; Post-crisis; Liquidity; Risk management; Banks